FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PADA SEKTOR KONSUMEN PRIMER 2019-2021 - Isabella, Ruth; Susanti, Merry; Cindy H. , Nastasya (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to empirically prove the effect of the variable Current Ratio (CR), Return on Assets (ROA), Total Asset Turnover (TATO), and asset structure to the variable capital structure in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange in 2019-2021. The sample was selected by purposive sampling method and the valid data are 39 companies. Data processing in this research used multiple regression analysis assisted by software program the Eviews version 12.0. The results of the research that had been carried out on the partial significance test showed that CR and asset structure had a significant effect on capital structure, but for ROA and TATO had no significant effect on capital structure. The implication of this research is the need to increased information for investors in making investment decisions and as a consideration for additional information about what factors influence capital structure so that it could assess company performance.